(untitled) (Research, Society and Development, 2022)
Biodegradable polyesters, such as the poly(lactic-co-glycolic acid) (PLGA), have been extensively used as a polymer matrix for entrapping a variety of active compounds. In this study, the physicochemical phenomena that control the mass transport mechanism of hydrophilic compounds released from PLGA microspheres were identified. This study aims to produce and characterize PLGA microspheres loaded with metformin hydrochloride (MH) and perform a case study using the literature data of PLGA microspheres loaded with fluorescein isothiocyanate-dextran (FITC-dextran). The MH is a low molecular weight compound that was easily and rapidly transported by diffusion mechanism through the microsphere pores. The FITC-dextran, as a high molecular weight compound, depended on the mechanism of polymer erosion and mesopore formation, with 18 days of duration, before its release by diffusion mass transfer. Values of the effective diffusion coefficient of MH and FITC-dextran, both in PLGA, were 2.4 x 10-13 and 5.3 x 10-18 m2 s-1, respectively, with a difference of five orders of magnitude attributed to the molecular weight of these hydrophilic compounds and the main mass transport that governed their release. This study provides important insights into the mechanisms of mass transfer and their correlation with the physicochemical properties of both hydrophilic compounds and the PLGA matrix, contributing to the development of biodegradable controlled delivery systems for a variety of applications in chemical, biotechnological, and pharmaceutical industries.